Decomposing lifetime-earnings differences between white, black, and hispanic families - Hope Bodenschatz; Gerald Eric Daniels; Jeffrey P. Thompson (Federal Reserve Bank of Boston, 2023)
This paper explores disparities between White, Black, and Hispanic families using a measure of lifetime earnings developed by Jacobs et al. (2022) for the Survey of Consumer Finances (SCF). Lifetime earnings are a particularly important measure of well-being, with relevance for wealth accumulation among other economic and social outcomes, but they are under-studied in the context of racial disparities. We describe how the different components of lifetime earnings-including annual earnings of workers, number of working household members, and number of years of employment during the working life-vary by race. We then decompose the differences in lifetime earnings using the recentered influence function and show that human capital-related variables, including educational attainment and years of full-time employment, account for most of the observed differences in lifetime earnings between White, Black, and Hispanic families. We also explore the contribution of business ownership to explained disparities in lifetime earnings and find that it is significant and that business ownership's explanatory power increases at the top of the lifetime-earnings distribution.
Keywords: D31; I31; J15; J24; J31; 330; Lifetime earnings; racial disparities; inequality